Single-Direction Approach for Thoracoscopic Segmentectomy of the Left Upper Lobe Anterior Segment With Mediastinal Lingular Artery. Issue 2 (March 2022) - Sueyoshi, Kuniyo; Kojima, Fumitsugu; Otsubo, Kosuke; Hirota, Shinya; Kitamura, Atsushi; Bando, Toru
Thoracoscopic resection of the anterior segment of the left upper lobe (S 3 ) is technically challenging because of the intricate hilar structure and multiple intersegmental planes to be dissected. A single-direction approach for S 3 segmentectomy is a technique in which surgeons dissect the hilum structures exclusively from the ventral side without dividing the interlobar fissure. Our consecutive case series and a representative surgical video demonstrated the feasibility of this approach in cases where the lingular artery arises from the first branch of the left pulmonary artery (mediastinal lingular artery).